PELATIHAN UMKM SEBAGAI UPAYA MENINGKATKAN LITERASI FINANSIAL MASYARAKAT DESA - Mulkan Ritonga; Rahma Muti'ah; Budianto Bangun; Dandi Febrian; Syahrol Sulaiman Ritonga (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
The emergence of public anxiety about new sources of income is the basis for implementing community service activities. This is due to the instability of the commodity prices of oil palm and rubber, which are the main incomes of the people of Tanjung Medan village. Various efforts to increase financial literacy have been carried out in various villages to increase community income sources as the spearhead of regional development. However, in Tanjung Medan Village there has never been a similar activity carried out and there are no MSMEs that have been established in the village. For this reason, financial literacy training activities were carried out in Tanjung Medan village. This activity aims to provide training for MSMEs to improve people's financial literacy through socialization and hands-on practical training. MSME training to improve financial literacy has proven to be applicable to rural communities. Training activities have been proven to stimulate public interest in forming MSMEs as the basis for increasing financial literacy in the form of new financial sources for the community. The implementation of the activity succeeded in providing new soft skills and hard skills for training participants. The results of the implementation of the activity provide new knowledge and the ability of participants in preparing and submitting a complete MSME formation. This activity also succeeded in providing new skills for the community, especially in making craft products made from rattan as well as various cakes and snacks.